The impact of a fasting mimicking diet on the metabolic health of a prospective cohort of patients with prostate cancer: a pilot implementation study - Fay-Watt, V.; O’Connor, S.; Roshan, D.; Romeo, A. C.; Longo, V. D.; Sullivan, F. J. (Prostate cancer and prostatic diseases, 2023)
Background This pilot prospective study investigated the effect of a periodic fasting mimicking diet (FMD) on metabolic health factors in patients with Prostate Cancer (PC). There is a well-documented association between PC and metabolic health. Impaired metabolic health is a significant risk factor for the development of PC, and a metabolic syndrome can be induced by hormonal therapies commonly required for its management. (ClinicalTrials.gov Identifier: NCT04292041). Methods We introduced a periodic 4-day FMD -low in calories, sugars, and proteins but high in unsaturated fats -to a cohort of PC patients and features of metabolic syndrome. 29/35 patients completed 3-monthly cycles of the 4-consecutive day packaged FMD. We compared the subjects’ baseline weight, abdominal circumference (AC), blood pressure (BP) and selected laboratory results to the same measurements 3-months after completing the FMD cycles. Results Several important metabolic factors showed improvements post-intervention. On average patients’ weights dropped by 3.79 kg (95% CI: −5.61, −1.97, p = 0.0002). AC was reduced on average by 4.57 cm, (95% CI: −2.27, −6.87, p = 0.0003). There was also a decrease in systolic and diastolic BP by 9.52 mmHg (95% CI: −16.16, −2.88, p = 0.0066) and 4.48 mmHg (95% CI: −8.85, −0.43, p = 0.0316) respectively. A sub-analysis indicates that FMD had more relevant effects in ‘at-risk’ patients than those with normal values of risk factors for metabolic syndrome. For example, subjects with baseline levels of systolic BP > 130 mmHg experienced a greater reduction in BP(−16.04 mmHg, p = 0.0001) than those with baseline systolic BP < 130 mmHg (−0.78 mmHg, p = 0.89). Conclusions The FMD cycles were safely introduced to this small cohort of PC patients with little or no observed toxicity, and a high overall compliance of 83%. Analysis of the metabolic variables showed an overall decrease in weight, AC, and BP. Larger clinical trials focused on metabolic risk factors, PC quality of life and progression free survival are needed to assess the effect of the FMD on prostate cancer patients.